GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 16 Dec 2018, 22:27

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel
Events & Promotions in December
PrevNext
SuMoTuWeThFrSa
2526272829301
2345678
9101112131415
16171819202122
23242526272829
303112345
Open Detailed Calendar
  • 10 Keys to nail DS and CR questions

     December 17, 2018

     December 17, 2018

     06:00 PM PST

     07:00 PM PST

    Join our live webinar and learn how to approach Data Sufficiency and Critical Reasoning problems, how to identify the best way to solve each question and what most people do wrong.
  • R1 Admission Decisions: Estimated Decision Timelines and Chat Links for Major BSchools

     December 17, 2018

     December 17, 2018

     10:00 PM PST

     11:00 PM PST

    From Dec 5th onward, American programs will start releasing R1 decisions. Chat Rooms: We have also assigned chat rooms for every school so that applicants can stay in touch and exchange information/update during decision period.

If 2x - 3y = 6, then 6y - 4x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 51230
If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 21 Aug 2018, 05:08
00:00
A
B
C
D
E

Difficulty:

  15% (low)

Question Stats:

80% (00:27) correct 20% (00:46) wrong based on 61 sessions

HideShow timer Statistics

Director
Director
User avatar
P
Joined: 18 Jul 2018
Posts: 502
Location: India
Concentration: Finance, Marketing
WE: Engineering (Energy and Utilities)
Premium Member Reviews Badge CAT Tests
Re: If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 21 Aug 2018, 05:12
Given 2x-3y = 6.
Multiply this by -2 gives 6y-4x = -12
A is the answer

Posted from my mobile device
_________________

When you want something, the whole universe conspires in helping you achieve it.

Board of Directors
User avatar
P
Status: QA & VA Forum Moderator
Joined: 11 Jun 2011
Posts: 4277
Location: India
GPA: 3.5
WE: Business Development (Commercial Banking)
GMAT ToolKit User Premium Member CAT Tests
Re: If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 21 Aug 2018, 10:22
Bunuel wrote:
If 2x - 3y = 6, then 6y - 4x =

A. -12
B. -6
C. 6
D. 12
E. Cannot be determined


\(\frac{6y - 4x}{-3y + 2x} = -2\)

So, The value of \(6y - 4x = -12\), Answer must be (A)
_________________

Thanks and Regards

Abhishek....

PLEASE FOLLOW THE RULES FOR POSTING IN QA AND VA FORUM AND USE SEARCH FUNCTION BEFORE POSTING NEW QUESTIONS

How to use Search Function in GMAT Club | Rules for Posting in QA forum | Writing Mathematical Formulas |Rules for Posting in VA forum | Request Expert's Reply ( VA Forum Only )

Director
Director
User avatar
P
Joined: 31 Oct 2013
Posts: 883
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 21 Aug 2018, 13:02
Bunuel wrote:
If 2x - 3y = 6, then 6y - 4x =

A. -12
B. -6
C. 6
D. 12
E. Cannot be determined



Given ,

2x - 3y = 6

6y - 4x = -12 ( multiply by -2 )

The best answer is A.
SVP
SVP
User avatar
D
Joined: 26 Mar 2013
Posts: 1919
Reviews Badge CAT Tests
Re: If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 22 Aug 2018, 04:39
Bunuel wrote:
If 2x - 3y = 6, then 6y - 4x =

A. -12
B. -6
C. 6
D. 12
E. Cannot be determined


6y - 4x = -2 (2x - 3y) = -2 * 6 =-12

Answer: A
Target Test Prep Representative
User avatar
P
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 4316
Location: United States (CA)
Re: If 2x - 3y = 6, then 6y - 4x =  [#permalink]

Show Tags

New post 23 Aug 2018, 15:59
Bunuel wrote:
If 2x - 3y = 6, then 6y - 4x =

A. -12
B. -6
C. 6
D. 12
E. Cannot be determined


Multiplying the given equation by -2, we have:

-4x + 6y = 6y - 4x = -12

Answer: A
_________________

Scott Woodbury-Stewart
Founder and CEO

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

GMAT Club Bot
Re: If 2x - 3y = 6, then 6y - 4x = &nbs [#permalink] 23 Aug 2018, 15:59
Display posts from previous: Sort by

If 2x - 3y = 6, then 6y - 4x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


Copyright

GMAT Club MBA Forum Home| About| Terms and Conditions and Privacy Policy| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.